Expression of soluble ST2 in patients with essential hypertension and its relationship with left ventricular hypertrophy - Peng Wei; Liang Liu; Xiaoqing Wang; Bin Zong; Xuekui Liu; Miaomiao Zhang; Qiang Fu; Liansheng Wang; Bangming Cao (ESC Heart Failure, 2023)
Abstract Aims Identification and intervention of left ventricular hypertrophy (LVH) in essential hypertension (EH) are important for the prevention of adverse cardiovascular events. However, effective methods for diagnosing LVH are still lacking. This study aimed to explore the relationship between soluble ST2 (sST2) and LVH in EH patients to identify a potential specific biomarker for hypertensive LVH. Methods and results This study included 97 EH patients. Based on the criteria for LVH, participants were divided into the LVH group (n = 52) and the non‐LVH group (n = 45). The level of serum sST2 was detected by enzyme‐linked immunosorbent assay. Pearson correlation analysis, logistic regression analysis, and receiver operating characteristic (ROC) curve analysis were used to investigate the potential of sST2 as a biomarker of LVH in EH patients. Compared with the non‐LVH group, the sST2 level was elevated in EH patients with LVH (P < 0.001). Pearson correlation analysis indicated that the sST2 level was positively correlated with the left ventricular mass index in EH patients (r = 0.454, P < 0.001). Logistic regression analysis showed that the odds ratio (OR) value of LVH was 2.990, suggesting that sST2 is an independent risk factor for LVH in EH patients [OR = 2.990, 95% confidence interval (CI), 1.650–5.419; P < 0.001]. The area under the ROC curve was 0.767 (95% CI, 0.669–0.866; P < 0.001), with a sensitivity of 0.808 and specificity of 0.689, indicating the possibility of considering sST2 as a biomarker for diagnosing LVH. Conclusions Up‐regulation of sST2 is strongly related to LVH in EH patients, is an independent risk factor for hypertensive LVH, and can be used as a biomarker for the diagnosis of LVH.